Cover Picture: Plasma Process. Polym. 1/2021. Issue 1 (14th January 2021) - Hojnik, Nataša; Modic, Martina; Žigon, Dušan; Kovač, Janez; Jurov, Andrea; Dickenson, Aaron; Walsh, James L.; Cvelbar, Uroš
Abstract : Cover Picture : The study demonstrates complete removal of aflatoxin B1 from the artificially contaminated corn kernels with an indirect cold atmospheric pressure plasma treatment generated with a surface barrier discharge system working in the ambient air. Furthermore, it presents the first step towards acceptance of plasma technology as a safe food processing method. Further details can be found in the article by Nataša Hojnik, Martina Modic, Dušan Žigon, Janez Kovač, Andrea Jurov, Aaron Dickenson, James L. Walsh, and Uroš Cvelbar (e2000163 ).